International legal cooperation in the Nazi-fascist New Order. Issue 6 (November 2018) - Martin, Benjamin
Abstract In the interwar history of the discipline of international law, the Nazi period was apparently nothing more than what Martti Koskenniemi calls a 'dark gap.' But the same cannot be said about international organizing in the law under Hitler. After reaching out to like-minded foreign jurists throughout the 1930s, Nazi jurists launched an international legal institution in 1939. Officially founded in 1941, the International Law Chamber (Internationale Rechtskammer ) created an international professional association that gathered jurists from across Europe in a transnational network, but one that rejected the liberal and universalist premises of international law. Instead, the organization used the 'soft power' of international intellectual exchange to promote a regional-European, anti-liberal, and fascist-corporatist vision of international legal order. During World War II, Nazi jurists used this network to pursue legal integration among the allied and conquered states included in Hitler's emerging European empire, thereby helping to build the Nazi 'New Order' in Europe.